Find y'' by implicit differentiation(adsbygoogle = window.adsbygoogle || []).push({});

x^4+y^4=1

i found that y'=-x^3/y^3

y''=[(y^3)(-3x^2)-(-x^3)(3y^2)(y')]/(y^3)^2

y''=[-3x^2(y^3)-(-x^3)(3y^2)(-x^3/y^3)]/y^6

then i am stuck...please help....thanks

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Find y'' by implicit differentiation

**Physics Forums | Science Articles, Homework Help, Discussion**